2009
DOI: 10.1089/cbr.2009.0660
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Defects and Functional Impairment in T-Cells from Cervical Cancer Patients

Abstract: The ability of T-lymphocytes to recognize antigens and transduce signals to the nucleus successfully is a key component in the initiation and maintenance of an immune response. The present study addressed the expression status of the signal-transducing proteins in relation to the immune impairment in cervical cancer patients. Immune response was measured by evaluating lymphocyte subpopulations CD3(+), CD4(+), and CD8(+), using flowcytometry, natural killer cell activity, using the single-cell cytotoxicity assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…When BV-associated strict anaerobes are able to colonise, they produce enzymes and metabolites, which may compromise this barrier, facilitating HPV entry. They also act on several cellular pathways that can enable a persistent, productive viral infection and subsequent disease development and progression [6872]. Indirect evidence generated by existing mechanistic studies in vivo and in vitro in complementary fields and models of BV, as well as studies of other viral genital infections, supports potential mechanisms that warrant further investigation.…”
Section: Potential Mechanisms Of Vaginal Microbiota-mediated Cervicalmentioning
confidence: 99%
“…When BV-associated strict anaerobes are able to colonise, they produce enzymes and metabolites, which may compromise this barrier, facilitating HPV entry. They also act on several cellular pathways that can enable a persistent, productive viral infection and subsequent disease development and progression [6872]. Indirect evidence generated by existing mechanistic studies in vivo and in vitro in complementary fields and models of BV, as well as studies of other viral genital infections, supports potential mechanisms that warrant further investigation.…”
Section: Potential Mechanisms Of Vaginal Microbiota-mediated Cervicalmentioning
confidence: 99%
“…It has been demonstrated that EPF can suppress the immune system by reducing T-cell proliferation and cytokine production (Rabinowich et al 1996;Reichert et al 1998;Cheriyan et al 2009). However, the contribution of EPF to Treg differentiation and function has not been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Zehbe et al 2007 showed that CD8+ cells specific for the HPV 16 E6 protein fail to control tumor growth despite interferon gamma production [33] suggesting that successful immune surveillance of HPV16+ tumor cells in cervical cancer patients is impaired. There are observations that those cells may be rendered tolerant by molecules present in tumor microenviroment [34,35]. Cervical tumors are marked by the presence of an immune regulatory microenvironment characterized by increased production of IL10 and TGFβ and decreased production of IL2 [31].…”
Section: Discussionmentioning
confidence: 99%